Role of adult education and mass media for civic education : report of the Asian Pacific seminar, New Delhi, September 10-14, 1985 - Saxena, J. C.; Sachdeva, J. L.; Unesco. Regional Office for Education in Asia and the Pacific; Asian-South Pacific Bureau of Adult Education; Indian Adult Education Association; Asian Pacific Seminar on the "Role of Adult Education and Mass Media for Civic Education" (1985 : New Delhi, India) (New Delhi : Indian Adult Education Association, 1986)
Papers and proceedings of the Asian Pacific Seminar on the "Role of Adult Education and Mass Media for Civic Education"
Cover title: Role of adult education & mass media for civic education
"Regional seminar was sponsored by UNESCO-ROEAP, ASPBAE, and IAEA"--T.p. verso
Includes bibliographies
Keywords: Adult education -- Asia -- Congresses; Adult education -- Pacific Area -- Congresses; Mass media in education -- Asia -- Congresses; Mass media in education -- Pacific Area -- Congresses; Civics -- Study and teaching -- Asia -- Congresses; Civics -- Study and teaching -- Pacific Area -- Congresses